2002
DOI: 10.1046/j.1365-2427.2002.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional and hierarchical perspectives of thermal regimes in subarctic, Alaskan lakes

Abstract: 1. We examined 60 clear, stained and glacial lakes in Alaska to quantify the relative importance of climate setting, morphometry, transparency, and lake typology influences on various thermal characteristics including duration of growing season, water temperature, mixing depth (MD) and heat content. We used analysis of variance (ANOVA) to test for differences in thermal characteristics in association with lake type and employed simple and multiple regression techniques to determine functional relationships bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 42 publications
2
39
0
Order By: Relevance
“…Recently, many studies have revealed a marked increment in the heat content, ABHB, and water temperature of natural lakes (MORTSCH and QUINN, 1996;STEFFAN et al, 1998;AMBROSETTI and BARBANTI, 1999;AMBROSETTI and BARBANTI, 2001;BLENCKNER, 2005), and have also stressed the importance of these calculations to our understanding of potential response of aquatic ecosystems to climate change (EDMUNSON and MAZUMDER, 2002). Interestingly, our results demonstrated that the hydraulic management applied to Sau Reservoir induced a progressive temporal reduction on the average temperature and heat content in the reservoir, thus counteracting the generalized warming trend.…”
Section: Discussionsupporting
confidence: 56%
“…Recently, many studies have revealed a marked increment in the heat content, ABHB, and water temperature of natural lakes (MORTSCH and QUINN, 1996;STEFFAN et al, 1998;AMBROSETTI and BARBANTI, 1999;AMBROSETTI and BARBANTI, 2001;BLENCKNER, 2005), and have also stressed the importance of these calculations to our understanding of potential response of aquatic ecosystems to climate change (EDMUNSON and MAZUMDER, 2002). Interestingly, our results demonstrated that the hydraulic management applied to Sau Reservoir induced a progressive temporal reduction on the average temperature and heat content in the reservoir, thus counteracting the generalized warming trend.…”
Section: Discussionsupporting
confidence: 56%
“…Since the pioneering work of Birge (1916), many studies have analyzed heat fluxes from lakes from around the world, including temperate lakes (Hutchinson and Edmondson, 1957), tropical lakes (Lewis, 1973), and subarctic lakes (Edmundson and Mazumder, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, surface-water temperature models reported in the literature typically incorporated lake morphology (e.g. Shuter et al, 1983;Shuter & Post, 1990;Snucins & Gunn, 2000;Edmundson & Mazumder, 2002;Kettle et al, 2004) and water chemistry variables, such as turbidity (e.g. Snucins & Gunn, 2000;Edmundson & Mazumder, 2002).…”
Section: Discussionmentioning
confidence: 99%